The use of thalidomide to treat children with tuberculosis meningitis: A review. (September 2021) - van Toorn, Ronald; Zaharie, Stefan-Dan; Seddon, James A.; van der Kuip, Martijn; Marceline van Furth, A.; Schoeman, Johan F.; Solomons, Regan S.
Abstract: Much of the morbidity and mortality caused by tuberculous meningitis (TBM) is mediated by a dysregulated immune response. Effective host-directed therapy is therefore critical to improve survival and clinical outcomes. Currently only one host-directed therapy (HDT), corticosteroids, is proven to improve mortality. However, there is no evidence that corticosteroids reduce morbidity and the mechanism of action for mortality reduction is uncertain. Further, it has no proven benefit in HIV co-infected individuals. One promising host-directed therapy approach is to restrict the immunopathology arising from tumour necrosis factor (TNF)-α excess is via TNF-α inhibitors. There are accumulating data on the role of thalidomide, anti -TNF-α monoclonal antibodies (infliximab, adalimumab) and the soluble TNF-α receptor (etanercept) in TBM treatment. Thalidomide was developed nearly seventy years ago and has been a highly controversial drug. Birth defects and toxic adverse effects have limited its use but an improved understanding of its immunological mechanism of action suggest that it may have a crucial role in regulating the destructive host response seen in inflammatory conditions such as TBM. Observational studies at our institution found low dosage adjunctive thalidomide safe in treating tuberculous mass lesions and blindness related to optochiasmatic arachnoiditis, with good clinical and radiological response. In this review, we discuss possible mechanisms of action for thalidomide, based on our clinico-radiologic experience and post-mortem histopathological work. We also propose a rationale for its use in the treatment of certain TBM-related complications.